ZnO / Bi2O3 composite photocatalyst as well as preparation method and application thereof

By introducing ZnO into the Bi2O3 photocatalyst, a Zn-O-Bi chemical bonding structure is formed, and a stable heterostructure is formed through low temperature plasma treatment, the problem of low efficiency of a single Bi2O3 photocatalyst is solved and efficient photocatalytic degradation performance is achieved.

CN119771392APending Publication Date: 2025-04-08QUANZHOU NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411938705.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The photogenerated electrons and hole separation rates of a single Bi2O3 photocatalyst are low, resulting in low photocatalytic reaction efficiency, limiting its promotion and application.

Method used

The precursor is formed by mixing Bi(NO3)3·5H2O and Zn(NO3)2·6H2O, and the oxidation-reduction reaction is carried out during the calcination process by adjusting the oxygen partial pressure to form a special chemical bonding structure of Zn-O-Bi. Subsequently, the interface is further activated and modified using a low-temperature plasma treatment to form a stable heterostructure.

Benefits of technology

The migration performance and photocatalytic activity of photogenerated carriers are improved, and the photocatalytic degradation performance of composite photocatalysts is enhanced in simulating the photocatalytic degradation performance of solar light excitation, especially in degrading the organic pollutant rhodamine B.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771392A_ABST
    Figure CN119771392A_ABST
Patent Text Reader

Abstract

The invention discloses a ZnO / Bi2O3 composite photocatalyst as well as a preparation method and application thereof, Bi (NO3) 3.5 H2O is added into a crucible, and Zn (NO3) 2.6 H2O is added into the crucible; adding a proper amount of distilled water into the crucible, carrying out ultrasonic treatment for 15-25 minutes, putting the crucible into a drying oven at 110-130 DEG C, and drying for 1.5-2.5 hours; the crucible is placed in a muffle furnace, the crucible is heated at the heating rate of 1.8-2.2 DEG C / min, a mixed atmosphere of oxygen and inert gas is introduced into the reaction chamber at the same time, in the initial stage, the partial pressure of the oxygen is larger than the partial pressure of the inert gas, when the temperature is increased to 200-300 DEG C, the partial pressure of the oxygen is gradually reduced, the partial pressure of the inert gas is gradually increased till the temperature is increased to 350-450 DEG C, calcination is conducted for 1.5-2.5 h, and the high-temperature-resistant ceramic is obtained. After cooling to room temperature, taking out and grinding; the preparation method comprises the following steps: putting the raw materials into low-temperature plasma treatment equipment for treatment, putting the treated raw materials into an inert atmosphere at 300-400 DEG C for annealing treatment, and drying at 60-80 DEG C to obtain the ZnO / Bi2O3 composite photocatalyst. The catalyst can degrade an organic pollutant rhodamine B solution, shows excellent photocatalytic degradation performance under simulated sunlight excitation, and is simple in preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalysts, and in particular to a ZnO / Bi2O3 composite photocatalyst and a preparation method and application thereof. Background Art

[0002] Water resource pollution in my country is mainly concentrated in industrial pollution, agricultural pollution and domestic pollution. It is well known that industrial production processes will produce high-concentration refractory organic wastewater, and the wastewater has various components, complex physical and chemical properties, and high toxicity. It is difficult to effectively treat it through ordinary biodegradation technology, adsorption technology, etc. If it is not treated properly, it will cause great damage and secondary pollution to the natural environment. As a research hotspot of advanced oxidation technology, photocatalytic technology has always been considered as one of the most promising advanced oxidation technologies for treating organic pollutants. It has the advantages of stability, pollution-free, clean and efficient, and low cost. It can degrade refractory organic pollutants into carbon dioxide, water, etc. Semiconductor photocatalysts have been developed in recent years and are one of the most ideal technologies that can effectively solve environmental pollution. The green, safe and non-secondary pollution-free nature of this technology has been deeply loved by scientific researchers.

[0003] Bi2O3 photocatalyst has the characteristics of good stability, environmental protection, wide light response range and low cost, which has attracted wide attention in the field of photocatalysis. However, there are certain shortcomings in the single Bi2O3 photocatalyst. The separation rate of photogenerated electrons and holes is low, resulting in low efficiency of photocatalytic reaction, which seriously limits the promotion and application of Bi2O3 photocatalyst. Therefore, other semiconductor materials are introduced into the Bi2O3 photocatalyst as a matrix to construct composite materials to solve the problem of low photocatalytic efficiency. ZnO photocatalyst has the characteristics of good photocatalytic activity and no secondary pollution, making it a hot spot in photocatalytic research. ZnO has good optical properties and suitable conduction band and valence band positions, which meet the conditions of the redox process of excellent photocatalysts and can promote the separation and transfer of photogenerated carriers. However, one of the strategies used by researchers to improve the visible light-driven Bi2O3 activity is to combine Bi2O3 with other semiconductors to obtain an effective heterostructure, which can enhance surface interactions, charge transfer and visible light response. Therefore, it is necessary to explore simpler, more efficient and controllable synthesis methods to prepare ZnO / Bi2O3 heterostructures with excellent performance. Summary of the invention

[0004] The purpose of the present invention is to provide a ZnO / Bi2O3 composite photocatalyst and a preparation method and application thereof, so as to solve the problems raised in the above background technology.

[0005] One of the technical solutions adopted by the present invention to solve the technical problem is:

[0006] Provided is a method for preparing a ZnO / Bi2O3 composite photocatalyst, comprising the following steps:

[0007] S1. Put Bi(NO3)3·5H2O in a crucible, and then add Zn(NO3)2·6H2O to the crucible; add an appropriate amount of distilled water to the crucible, ultrasonicate for 15-25 minutes, place in an oven at 110-130°C, and dry for 1.5-2.5 hours;

[0008] S2, placing the crucible in a muffle furnace, heating it at a heating rate of 1.8-2.2°C / min, and introducing a mixed atmosphere of oxygen and inert gas into the reaction chamber. In the initial stage, the oxygen partial pressure is greater than the inert gas partial pressure. When the temperature rises to 200-300°C, the oxygen partial pressure is gradually reduced, and the inert gas partial pressure is gradually increased until the temperature rises to 350-450°C, and then calcined for 1.5-2.5h, and after it cools to room temperature, it is taken out and ground;

[0009] S3, placing it in a low-temperature plasma treatment device for treatment, placing it in an inert atmosphere at 300-400° C. for annealing after treatment, and drying it at 60-80° C. to obtain a ZnO / Bi2O3 composite photocatalyst.

[0010] Furthermore, in S2, in the initial stage, the partial pressure of oxygen is 0.5-0.6 atm, and the partial pressure of the inert gas is 0.4-0.5 atm.

[0011] Furthermore, in S2, when the temperature rises to 200-300°C, the partial pressure of oxygen is 0.1-0.2 atm, and the partial pressure of the inert gas is 0.8-0.9 atm.

[0012] Furthermore, the molar ratio of Bi(NO3)3·5H2O to Zn(NO3)2·6H2O is 4.1:1.3-3.9.

[0013] Furthermore, in the low-temperature plasma equipment, the flow rate of the inert gas is 30 to 50 mL / min.

[0014] Furthermore, the plasma power is 100-300W.

[0015] Furthermore, the plasma treatment time is 20 to 30 minutes.

[0016] The second technical solution adopted by the present invention to solve its technical problem is:

[0017] Provided is a ZnO / Bi2O3 composite photocatalyst, which is prepared by the above-mentioned preparation method of the ZnO / Bi2O3 composite photocatalyst.

[0018] The third technical solution adopted by the present invention to solve its technical problem is:

[0019] Provided is a method for preparing the ZnO / Bi2O3 composite photocatalyst as described above, and the application of the ZnO / Bi2O3 composite photocatalyst in removing Rhodamine B.

[0020] Furthermore, the application method includes: adding the prepared ZnO / Bi2O3 composite photocatalyst to a solution containing tetracycline, continuously stirring and dark adsorbing for 50 to 70 minutes to make the ZnO / Bi2O3 composite photocatalyst adsorb / desorb in equilibrium, after the dark adsorption is completed, performing a visible light catalytic reaction under a xenon lamp, reacting for 20 to 90 minutes, filtering and separating, and removing rhodamine B in the solution.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention solves the problem of low efficiency of the existing single photocatalyst, especially the problem of low separation and transfer efficiency of photogenerated carriers in Bi2O3 catalytic materials. First, Bi(NO3)3·5H2O and Zn(NO3)2·6H2O are mixed and treated to form a precursor. During the calcination process, due to the reduction of oxygen partial pressure, a partial oxidation-reduction reaction occurs at the interface between ZnO and Bi2O3 to form a special chemical bonding structure of Zn-O-Bi. This chemical bonding can effectively adjust the electronic structure at the interface, reduce the energy barrier at the interface, and promote the migration of photogenerated carriers between ZnO and Bi2O3. The interface is further activated and finely modified by high-energy particles in low-temperature plasma. Plasma treatment can generate a large number of active sites on the catalyst surface, interact with the chemical bonding structure at the interface, further adjust the electronic state of the interface, make the chemical bonding at the interface more regular, form a thin surface layer with antioxidant and corrosion resistance, form a stable heterogeneous structure, reduce the carrier migration barrier, enhance the transmission performance of photogenerated carriers at the interface, and then promote the interface to a more stable state through heat treatment, reduce the stress and defects inside the crystal, which is more conducive to the migration of photogenerated carriers inside the crystal, thereby improving its photocatalytic activity. The composite photocatalyst can degrade the organic pollutant Rhodamine B solution and exhibit excellent photocatalytic degradation performance under simulated sunlight excitation. The preparation method is simple and easy to operate, which is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 XRD diagrams of samples prepared in Examples 1 to 6 of the present invention;

[0023] Figure 2 This is a SEM image of the sample prepared in Example 4 of the present invention;

[0024] Figure 3This is a graph showing the degradation rates of Rhodamine B for different catalysts prepared in Examples 1 to 6 of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1: Preparation of ZnO material

[0027] Weigh 11.8 mmol of Zn(NO3)2·6H2O sample into a crucible, place the crucible in a muffle furnace, heat it at a heating rate of 2°C / min, and finally raise it to 400°C. Then calcine it for 2 hours. After it cools to room temperature, take out the catalyst and grind it to obtain a ZnO catalyst.

[0028] Example 2: Preparation of Bi2O3 photocatalyst

[0029] Bi2O3 was prepared by calcination method. 4.1 mmol of Bi(NO3)3·5H2O sample was weighed into a crucible, and the crucible was placed in a muffle furnace and heated at a heating rate of 2°C / min to 400°C. It was then calcined for 2 hours. After it cooled to room temperature, the catalyst was taken out and ground to obtain Bi2O3 catalyst.

[0030] Example 3: Preparation of ZnO / Bi2O3 composite photocatalyst

[0031] Bi(NO3)3·5H2O is placed in a crucible, and then Zn(NO3)2·6H2O is added to the crucible; an appropriate amount of distilled water is added to the crucible, and after ultrasonic treatment for 15 to 25 minutes, it is ensured that the solid is dissolved and mixed evenly, and the mixed solution is placed in an oven at 110 to 130°C and dried for 1.5 to 2.5 hours to evaporate the solvent to form a solid precursor, and the crucible is placed in a muffle furnace and heated at a heating rate of 1.8 to 2.2°C / min, and a mixed atmosphere of oxygen and inert gas is introduced into the reaction chamber. In the initial stage, the oxygen partial pressure is relatively high. For example, when the total gas pressure is 1 atm, the oxygen partial pressure is set to 0.5 to 0.6 atm, and the inert gas partial pressure is 0.4 to 0.5 atm. At this stage, as the temperature rises, Zn(NO3)2·6H2O and Bi(NO3)3·5H2O begin to gradually decompose to form precursor substances of ZnO and Bi2O3, and due to the higher oxygen partial pressure, some metal ions may be oxidized to a higher valence state to form some intermediate states of oxides. When the temperature rises to 200-300°C, the oxygen partial pressure is gradually reduced and the inert gas partial pressure is gradually increased. For example, the oxygen partial pressure is reduced to 0.1-0.2atm, and the inert gas partial pressure is correspondingly increased to 0.8-0.9atm. At this time, due to the decrease in oxygen partial pressure, partial oxidation-reduction reaction will occur at the interface of ZnO and Bi2O3. The Zn ions in ZnO may be partially reduced, while the Bi ions in Bi2O3 may be partially oxidized, forming a special chemical bonding structure of Zn-O-Bi. This chemical bonding can effectively adjust the electronic structure at the interface, reduce the energy barrier at the interface, and promote the migration of photogenerated carriers between ZnO and Bi2O3 until the temperature rises to 350-450°C, and then calcined for 1.5-2.5 hours to allow the reaction to proceed fully and the crystal structure to be further improved. After the calcination is completed, the heating is stopped, and the sample is naturally cooled to room temperature under the protection of inert gas to prevent the sample from being oxidized or contaminated by other impurities during the cooling process. The sample is taken out and ground; the sample treated with oxygen partial pressure is placed in a low-temperature plasma treatment device for treatment. Taking oxygen-argon mixed plasma as an example, the power of the plasma treatment body is adjusted to 100-300W, the flow rate of the inert gas is 30-50mL / min, and the treatment time is 20-30min. During the plasma treatment process, high-energy argon ions and active oxygen ions (such as O - 、O2 -) bombards the surface of the photocatalyst, generates a large number of active sites on the catalyst surface, such as oxygen vacancies, unsaturated chemical bonds, etc., which interact with the chemical bonding structure at the interface. For example, oxygen vacancies can adsorb oxygen molecules, and the adsorbed oxygen molecules participate in the reaction of the ZnO and Bi2O3 interface, promote the formation of a special chemical bonding structure, and the unsaturated chemical bonds participate in the reaction of the ZnO and Bi2O3 interface, promote the formation of a special chemical bonding structure, further adjust the electronic state of the interface, make the chemical bonding at the interface more regular, form a thin surface layer with antioxidant and corrosion resistance, form a stable heterogeneous structure, reduce the carrier migration barrier, enhance the transmission performance of photogenerated carriers at the interface, and place the plasma treated in an inert atmosphere at 300-400°C for annealing, so as to promote the interface to a more stable state, reduce the stress and defects inside the crystal, thereby being more conducive to the migration of photogenerated carriers inside the crystal, and finally dried at 60-80°C to obtain a ZnO / Bi2O3 composite photocatalyst.

[0032] In this embodiment, 4.1 mmol of Bi(NO3)3·5H2O was placed in a crucible, and then 1.3 mmol of Zn(NO3)2·6H2O was added to the crucible; 2 mL of distilled water was added to the crucible, and after ultrasonic treatment for 20 min, it was placed in a 120°C oven and dried for 2 h. The crucible was placed in a muffle furnace and heated at a heating rate of 2°C / min. At the same time, a mixed atmosphere of oxygen and inert gas was introduced into the reaction chamber. In the initial stage, the oxygen partial pressure was set to 0.55 atm and the inert gas partial pressure was 0.45 atm. When the temperature was raised to 250°C, the oxygen partial pressure was gradually reduced, and the inert gas partial pressure was gradually increased to reduce the oxygen partial pressure to 0.1 5atm, the inert gas partial pressure is correspondingly increased to 0.85atm, until the temperature rises to 400℃, and then calcined for 2h. After the calcination is completed, the heating is stopped, and the sample is naturally cooled to room temperature under the protection of inert gas, taken out and ground; the sample treated with oxygen partial pressure is placed in a low-temperature plasma treatment equipment for treatment. Taking oxygen-argon mixed plasma as an example, the power of the plasma treated body is adjusted to 200w, the flow rate of the inert gas is 40mL / min, and the treatment time is 25min. The plasma-treated body is placed in an inert atmosphere at 350℃ for annealing, and finally dried at 70℃ to obtain a ZnO / Bi2O3 composite photocatalyst, recorded as BZ-1.

[0033] Example 4: Preparation of ZnO / Bi2O3 composite photocatalyst

[0034] The preparation method of this embodiment is the same as that of Example 3, except that the amount of Zn(NO3)2·6H2O added in the steps of Example 3 is changed from 1.3 mmol to 2.1 mmol, and the remaining steps are the same as those of Example 3. The obtained ZnO / Bi2O3 composite photocatalyst sample is recorded as BZ-2.

[0035] Example 5: Preparation of ZnO / Bi2O3 composite photocatalyst

[0036] The preparation method of this embodiment is the same as that of Example 3, except that the amount of Zn(NO3)2·6H2O added in the steps of Example 3 is changed from 1.3 mmol to 2.9 mmol, and the remaining steps are the same as those of Example 3. The obtained ZnO / Bi2O3 composite photocatalyst sample is recorded as BZ-3.

[0037] Example 6: Preparation of ZnO / Bi2O3 composite photocatalyst

[0038] The preparation method of this embodiment is the same as that of Example 3, except that the amount of Zn(NO3)2·6H2O added in the steps of Example 3 is changed from 1.3 mmol to 3.9 mmol, and the remaining steps are the same as those of Example 3. The obtained ZnO / Bi2O3 composite photocatalyst sample is recorded as BZ-4.

[0039] In order to understand the composition and structure of each sample, scanning electron microscopy (SEM) and X-ray diffractometer (XRD) were used to characterize the samples.

[0040] Experimental Example 1: Diffraction Pattern Analysis

[0041] The samples prepared in Examples 1 to 6 were subjected to X-ray diffraction by continuous spectrum scanning using an X-ray diffractometer, with a scanning range of 0° to 80° and a scanning rate of 2° / min. The diffraction patterns were analyzed to study the composition of the material and the structural morphology of atoms or molecules inside the material, and to determine whether the preparation was successful.

[0042] X-ray diffraction is widely used to characterize the intercalation structure of polymer / layered nanocomposites. The position of the diffraction peak in the XRD spectrum can reflect the size of the polymer interlayer spacing. Figure 1 The XRD diagrams of the samples prepared in Examples 1 to 6 show that the prepared materials exhibit characteristic diffraction peaks of ZnO and Bi2O3, indicating that ZnO, Bi2O3 and ZnO / Bi2O3 composite photocatalysts have been prepared.

[0043] Test Example 2: Scanning electron microscope analysis

[0044] The BZ-2 sample was scanned by a scanning electron microscope to observe the microstructure of the BZ-2 sample.

[0045] Figure 2 This is the SEM image of the BZ-2 sample, which shows the morphology of ZnO nanosheets and Bi2O3 samples wrapped together.

[0046] Test Example 3: Evaluation of photocatalytic degradation performance

[0047] 40 mg of the catalyst was added to 80 ml of 10 ppm Rhodamine B solution, and the mixture was stirred and dark adsorbed for 60 minutes to ensure the adsorption / desorption balance of the catalyst. After the dark adsorption was completed, the xenon lamp was turned on. After a certain period of time, 4 ml of the reaction solution was centrifuged and the supernatant was tested on a UV-visible spectrophotometer. The experimental results are shown in Figure 3 .

[0048] Figure 3 The degradation diagram of Rhodamine B of different catalysts prepared in Examples 1 to 7 is shown in the figure. It can be seen from the figure that the photocatalytic activity of the ZB-2 sample is the highest, that is, when the molar ratio of ZnO to Bi2O3 is close to 1:2, its photocatalytic activity is the highest, and after 90 minutes of visible light excitation, its degradation rate can reach 93%, indicating that the prepared ZnO / Bi2O3 composite photocatalyst is an efficient photocatalyst.

[0049] The present invention solves the problem of low efficiency of existing single photocatalysts, especially the problem of low separation and transfer efficiency of photogenerated carriers in Bi2O3 catalytic materials. First, Bi(NO3)3·5H2O and Zn(NO3)2·6H2O are mixed to form a precursor. During the calcination process, due to the reduction of oxygen partial pressure, a partial oxidation-reduction reaction occurs at the interface of ZnO and Bi2O3 to form a special chemical bonding structure of Zn-O-Bi. This chemical bonding can effectively adjust the electronic structure at the interface, reduce the energy barrier at the interface, and promote the migration of photogenerated carriers between ZnO and Bi2O3. The high-energy particles in the daughter body further activate and finely modify the interface. Plasma treatment can generate a large number of active sites on the catalyst surface, interact with the chemical bonding structure at the interface, further adjust the electronic state of the interface, make the chemical bonding at the interface more regular, form a thin surface layer with antioxidant and corrosion resistance, form a stable heterogeneous structure, reduce the carrier migration barrier, enhance the transmission performance of photogenerated carriers at the interface, and then promote the interface to a more stable state through heat treatment, reduce the stress and defects inside the crystal, which is more conducive to the migration of photogenerated carriers inside the crystal, thereby improving its photocatalytic activity. The composite photocatalyst can degrade the organic pollutant Rhodamine B solution and exhibit excellent photocatalytic degradation performance under simulated sunlight excitation. The preparation method is simple and easy to operate, which is suitable for promotion and application.

[0050] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a ZnO / Bi2O3 composite photocatalyst, characterized in that: The following steps are involved: S1. Put Bi(NO3)3·5H2O in a crucible, and then add Zn(NO3)2·6H2O to the crucible; add an appropriate amount of distilled water to the crucible, ultrasonicate for 15-25 minutes, place in an oven at 110-130°C, and dry for 1.5-2.5 hours; S2, placing the crucible in a muffle furnace, heating it at a heating rate of 1.8-2.2°C / min, and introducing a mixed atmosphere of oxygen and inert gas into the reaction chamber. In the initial stage, the oxygen partial pressure is greater than the inert gas partial pressure. When the temperature rises to 200-300°C, the oxygen partial pressure is gradually reduced, and the inert gas partial pressure is gradually increased until the temperature rises to 350-450°C, and then calcined for 1.5-2.5h, and after it cools to room temperature, it is taken out and ground; S3, placing it in a low-temperature plasma treatment device for treatment, placing it in an inert atmosphere at 300-400° C. for annealing after treatment, and drying it at 60-80° C. to obtain a ZnO / Bi2O3 composite photocatalyst.

2. The method for preparing the ZnO / Bi2O3 composite photocatalyst according to claim 1, characterized in that: In S2, in the initial stage, the partial pressure of oxygen is 0.5-0.6 atm, and the partial pressure of the inert gas is 0.4-0.5 atm.

3. The method for preparing the ZnO / Bi2O3 composite photocatalyst according to claim 1 or 3, characterized in that: In S2, when the temperature rises to 200-300°C, the partial pressure of oxygen is 0.1-0.2 atm, and the partial pressure of inert gas is 0.8-0.9 atm.

4. The method for preparing the ZnO / Bi2O3 composite photocatalyst according to claim 1, characterized in that: The molar ratio of Bi(NO3)3·5H2O to Zn(NO3)2·6H2O is 4.1:1.3-3.

9.

5. The method for preparing the ZnO / Bi2O3 composite photocatalyst according to claim 1, characterized in that: In the low-temperature plasma equipment, the flow rate of the inert gas is 30 to 50 mL / min.

6. The method for preparing the ZnO / Bi2O3 composite photocatalyst according to claim 1, characterized in that: The plasma power is 100-300W.

7. The method for preparing the ZnO / Bi2O3 composite photocatalyst according to claim 1, characterized in that: The plasma treatment time is 20 to 30 minutes.

8. A ZnO / Bi2O3 composite photocatalyst, characterized in that: The photocatalyst is prepared by the preparation method of the ZnO / Bi2O3 composite photocatalyst according to any one of claims 1 to 7.

9. A method for preparing a ZnO / Bi2O3 composite photocatalyst as claimed in any one of claims 1 to 7, wherein the ZnO / Bi2O3 composite photocatalyst is used for removing Rhodamine B.

10. The use of the ZnO / Bi2O3 composite photocatalyst in removing Rhodamine B according to claim 9, characterized in that: The application method comprises: adding the prepared ZnO / Bi2O3 composite photocatalyst to a solution containing rhodamine B, continuously stirring and dark adsorbing for 50 to 70 minutes to achieve adsorption / desorption equilibrium of the ZnO / Bi2O3 composite photocatalyst, after the dark adsorption is completed, performing a visible light catalytic reaction under a xenon lamp, reacting for 20 to 90 minutes, filtering and separating, and removing rhodamine B in the solution.